2021
DOI: 10.3390/nano11071771
|View full text |Cite
|
Sign up to set email alerts
|

Current Developments in Native Nanometric Discoidal Membrane Bilayer Formed by Amphipathic Polymers

Abstract: Unlike cytosolic proteins, membrane proteins (MPs) are embedded within the plasma membrane and the lipid bilayer of intracellular organelles. MPs serve in various cellular processes and account for over 65% of the current drug targets. The development of membrane mimetic systems such as bicelles, short synthetic polymers or amphipols, and membrane scaffold proteins (MSP)-based nanodiscs has facilitated the accommodation of synthetic lipids to stabilize MPs, yet the preparation of these membrane mimetics remain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 98 publications
(119 reference statements)
0
6
0
Order By: Relevance
“…Nanodiscs are membrane mimetic systems formed from a membrane scaffold protein, exogenous lipids and the target protein, with the scaffold protein wrapping around the complex of lipids and protein. This arrangement shields the protein from aqueous solution and produces a more native-like environment than detergent micelles whilst also allowing ready variation of the lipid composition [80,81]. The results of the study on LacY and XylE revealed that in the presence of PE both transporters were preferentially in the inward-facing conformational state.…”
Section: The Major Facilitator Superfamily Sugar Transporters Lacy and Xylementioning
confidence: 99%
“…Nanodiscs are membrane mimetic systems formed from a membrane scaffold protein, exogenous lipids and the target protein, with the scaffold protein wrapping around the complex of lipids and protein. This arrangement shields the protein from aqueous solution and produces a more native-like environment than detergent micelles whilst also allowing ready variation of the lipid composition [80,81]. The results of the study on LacY and XylE revealed that in the presence of PE both transporters were preferentially in the inward-facing conformational state.…”
Section: The Major Facilitator Superfamily Sugar Transporters Lacy and Xylementioning
confidence: 99%
“…However, detergent solubilization can be too harsh for membrane proteins or complexes as the detergent strips the majority of endogenous lipids and cofactors from the proteins. Several approaches for relipidating the detergent solubilized membrane protein and reconstituting it into a bilayer mimicking environment have been developed, including membrane scaffold protein (MSP) nanodiscs, saposin-lipoprotein (Salipro) nanoparticles, and peptidiscs. In recent years, amphiphilic copolymers have emerged as an attractive alternative to detergents, as they enable direct solubilization of membrane proteins encapsulated by a patch of the surrounding lipid bilayer from the membrane into so-called native nanodiscs. , With the native nanodisc approach, the membrane protein remains lipidated, and endogenous lipids and cofactors are preserved around it. Styrene-maleic acid (SMA) copolymers (Figure A) were the first to be used for the generation of native nanodiscs, and their use remains widespread. , While the native nanodisc approach shows great promise, there are significant shortcomings with the currently used copolymers. These include their negative charge and heterogeneity in terms of molecular weight and monomer sequence, which altogether limit the applicability of the method to a wider range of protein targets .…”
Section: Introductionmentioning
confidence: 99%
“…Alternative copolymers, which try to ameliorate these challenges have been published, including poly­(diisobutylene- co -maleic acid) (DIBMA), polymethacrylate (PMA), stilbene–maleic anhydride (STMA), and various SMA derivative copolymers, as well as a noncharged inulin derivative . The current developments in native nanodiscs have recently been reviewed by, e.g., Brown et al and Esmaili et al…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations